Could gestational diabetes mellitus be managed through dietary bioactive compounds? Current knowledge and future perspectives. Issue 7 (16th February 2016) - Santangelo, Carmela; Zicari, Alessandra; Mandosi, Elisabetta; Scazzocchio, Beatrice; Mari, Emanuela; Morano, Susanna; Masella, Roberta
Abstract: Gestational diabetes mellitus (GDM) is a serious problem growing worldwide that needs to be addressed with urgency in consideration of the resulting severe complications for both mother and fetus. Growing evidence indicates that a healthy diet rich in fruit, vegetables, nuts, extra-virgin olive oil and fish has beneficial effects in both the prevention and management of several human diseases and metabolic disorders. In this review, we discuss the latest data concerning the effects of dietary bioactive compounds such as polyphenols and PUFA on the molecular mechanisms regulating glucose homoeostasis. Several studies, mostly based on in vitro and animal models, indicate that dietary polyphenols, mainly flavonoids, positively modulate the insulin signalling pathway by attenuating hyperglycaemia and insulin resistance, reducing inflammatory adipokines, and modifying microRNA (miRNA) profiles. Very few data about the influence of dietary exposure on GDM outcomes are available, although this approach deserves careful consideration. Further investigation, which includes exploring the 'omics' world, is needed to better understand the complex interaction between dietary compounds and GDM.